2015
DOI: 10.1177/1358863x15614388
|View full text |Cite
|
Sign up to set email alerts
|

Four key questions surrounding thrombolytic therapy for submassive pulmonary embolism

Abstract: Submassive pulmonary embolism (PE) remains a vexing entity, and the appropriate use of thrombolytic therapy for this subgroup continues to be actively debated. Catheter-directed thrombolysis has shown efficacy for submassive PE and is gaining momentum because of theoretically improved safety. This review poses and responds to four questions that explore the complex issues surrounding optimal therapy of submassive PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…7 It should be mentioned that since this registry data, several randomized control trials have demonstrated significantly lower 90-day mortality rates for submassive PE (2-3%). 8…”
Section: Submassive Pulmonary Embolism Epidemiology and Natural Historymentioning
confidence: 99%
See 2 more Smart Citations
“…7 It should be mentioned that since this registry data, several randomized control trials have demonstrated significantly lower 90-day mortality rates for submassive PE (2-3%). 8…”
Section: Submassive Pulmonary Embolism Epidemiology and Natural Historymentioning
confidence: 99%
“…Determining which submassive PE patients should be considered for escalation of therapy is an ongoing research topic. 8 The ESC system of stratifying intermediate PE patients Fig. 3 Results from PERFECT, SEATTLE II, and ULTIMA trials demonstrating similar mean systolic pulmonary artery pressures, at baseline and after intervention with CDT.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal management of submassive pulmonary embolism (PE) is uncertain. Submassive PE is associated with a higher rate of clinical deterioration and mortality compared to low-risk PE when treated with anticoagulation alone [1,2,3,4]. Survivors may also suffer from a long-term “post-PE syndrome” (PPS) and chronic thromboembolic pulmonary hypertension (CTEPH), characterized by decreased exercise tolerance and quality of life [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Targeted delivery of a low-dose thrombolytic drug into the clot through a multi-side hole catheter could mitigate the risk of major bleeding complications while achieving better drug effectiveness [8]. However, CDT’s efficacy and safety have been inadequately evaluated [1,2,9,10,11].…”
Section: Introductionmentioning
confidence: 99%